2011
DOI: 10.1186/1748-5908-6-124
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the effects of a multifaceted intervention to improve inpatient care in rural Kenyan hospitals - interpretation based on retrospective examination of data from participant observation, quantitative and qualitative studies

Abstract: BackgroundWe have reported the results of a cluster randomized trial of rural Kenyan hospitals evaluating the effects of an intervention to introduce care based on best-practice guidelines. In parallel work we described the context of the study, explored the process and perceptions of the intervention, and undertook a discrete study on health worker motivation because this was felt likely to be an important contributor to poor performance in Kenyan public sector hospitals. Here, we use data from these multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 54 publications
2
76
0
Order By: Relevance
“…One randomised controlled trial (Level II) [42] and two Level I qualitative studies were identified [35,65]. …”
Section: Resultsmentioning
confidence: 99%
“…One randomised controlled trial (Level II) [42] and two Level I qualitative studies were identified [35,65]. …”
Section: Resultsmentioning
confidence: 99%
“…She had previously conducted qualitative research [16-20]. Her background enabled her to take participatory roles in different capacities; as a consultant paediatrician, academic, ETAT+ trainer and as a researcher conducting an action oriented ethnographic study.…”
Section: Methodsmentioning
confidence: 99%
“…Its decline of 3/4 between 2000 and 2015 constituted number Five of the Millennium Development Goals (MDGs) developed by UN [1]. However, a recent evaluation showed a very slow evolution of indicators in sub-Saharan Africa [2] with significant disparities between West and Central Africa [2]. In Senegal, by 2015, the maternal mortality ratio was 315 maternal deaths per 100,000 live births [3], while the target was 139, a difference of 253 points from the 2015 target [3].…”
Section: Introductionmentioning
confidence: 99%